2022
DOI: 10.1007/s00213-021-05958-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics changes in brain-gut axis after unpredictable chronic mild stress

Abstract: Background Major depressive disorder is a leading cause of disability worldwide, affecting up to 17 % of the general population. The neural mechanisms of depression, however, are yet to be uncovered. Recently, attention has been drawn to the effects of dysfunctional brain-gut axis on depression, and many substances have been suggested to be involved in the communication between the gut and brain, such as ghrelin. Methods We herein systematically examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Tremendous progress has been made in studying the bidirectional interactions between the gastrointestinal tract and the central nervous system [ 56 ], and understanding the interaction between the digestive system with the brain may provide novel approaches for prevention and treatment of MDD [ 57 , 58 ]. Indeed, the digestive system has also been found to play an important role in MDD, including liver [ 59 , 60 ] and intestine [ 61 ].…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
“…Tremendous progress has been made in studying the bidirectional interactions between the gastrointestinal tract and the central nervous system [ 56 ], and understanding the interaction between the digestive system with the brain may provide novel approaches for prevention and treatment of MDD [ 57 , 58 ]. Indeed, the digestive system has also been found to play an important role in MDD, including liver [ 59 , 60 ] and intestine [ 61 ].…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
“…Furthermore, 5-HT levels can be affected by three neurobiologically related factors of PSD: increased inflammation and trauma, decreased cerebral brain-derived neurotrophic factor (BDNF), and dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis. Raison et al ( 87 ) reported that the metabolisms of 5-HT are affected by the central nervous system (CNS) inflammatory response ( 88 ). A peripherally administered cytokine could activate a CNS inflammatory response in humans that interacted with 5-HT metabolism, which was associated with depression.…”
Section: Monoamine Transmitters In the Treatment Of Psdmentioning
confidence: 99%
“…In spite of its central importance for human beings, emotion is still one of the least studied subjects among the life sciences (Gu et al, 2016 ). Even though the last century has witnessed many progresses in emotional studies, psychological analyses have not resolved many of the core issues surrounding emotions (Xu et al, 2022 ), such as the number of basic emotions, and the definition of basic emotions. Although there has been no shortage of psychological research on these debates, for instance, there is little agreement about how many emotions are “basic,” which emotions are “basic,” and why they are “basic” (Liang et al, 2021 ).…”
mentioning
confidence: 99%
“…Many scientists started to identify the neural structures that are responsible for particular emotions in the mid-twentieth century, and found that the limbic system might be the brain locus for emtions, and called Papez circuit the emotional brain. These pioneering work outlined the neural anatomical basis of emotion, and helped locate many important structures involved in basic emotions, such as the amygdala, which might be the place for fearful emotions (Xu et al, 2022 ). However, these investigations stopped with the development of behaviorism, which suggested that emotion is not a kind of behavior that can be objectively studied in the laboratory, because of its introspection nature.…”
mentioning
confidence: 99%